The effect of motivation and work environment on the performance of dental and oral therapists in dental hospitals in Yogyakarta - Selviasari, Chyca; Hendrartini, Julita; Hanindriyo, Lisdrianto (Majalah Kedokteran Gigi Indonesia, 2023)
Dental and oral therapists are medical workers who work in dental hospitals and play an important role in improving dental and oral health with members of work teams, such as dentists and other medical workers. Factors which influence their performance include motivation and work environment. The present study aims to determine the relation between motivation and work environment of dental and oral therapists working in dental hospitals. The present study was mix method research with explanatory sequential design and used total sampling method. The research subjects were 30 dental and oral therapist respondents who worked in 2 dental hospitals. A total of 19 participants worked at Prof. Soedomo Dental Hospital of Universitas Gadjah Mada, while eleven participants worked at Muhammadiyah Yogyakarta University Dental Hospital. The independent variables were motivation and physical and non-physical work environments. The dependent variable was performance of dental and oral therapist. The measurement was a questionnaire about motivation, and physical and non-physical work environments. Data analysis was conducted using a quantitative parametric measure of Pearson’s correlation test because the data was normally distributed, while qualitative analysis used interview. We found that there was no relation between motivation and performance (p > 0.05), no relation between non-physical work environment and performance (p > 0.05), and no relation between physical work environment and performance (p > 0.05). Qualitative results based on interviews with the dental and oral therapists showed that they had high motivation because they were proud, and they had good perception of the non-physical work environment due to solid work team. They also had good perception of the physical work environment because it was comfortable and had good facilities. Overall, motivation and work environment do not affect the performance of dental and oral therapists working in dental hospitals.